2017
DOI: 10.1055/s-0043-112249
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of B-Mode with B-Flow Sonography for the Evaluation of Femoral Arteries in Infants

Abstract: To evaluate femoral arteries (FAs) in infants in the context of catheter angiography with B-mode (BMS) and B-flow sonography (BFS) and to compare both methods for vessel delineation and reliability of vessel diameter measurements. 21 consecutive infants who underwent ultrasound for the evaluation of FAs before or after cardiac catheterization were retrospectively included in this study. The diameter of the FAs and the maximum length of the vessel section displayed on a single ultrasound plane were recorded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In summary, BFS yields better results than CDS for assessing the overall vascularity in pediatric kidney transplantation and thereby could improve monitoring of transplant viability. As suggested by previous studies focusing on other vascular territories, the B-flow technique may be especially useful in infants and young children [18,19]. BFS is less favorable in larger patients and for the deeper parts of the kidney due to sound beam attenuation and should thereby be used in addition to Dopplerbased ultrasound techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, BFS yields better results than CDS for assessing the overall vascularity in pediatric kidney transplantation and thereby could improve monitoring of transplant viability. As suggested by previous studies focusing on other vascular territories, the B-flow technique may be especially useful in infants and young children [18,19]. BFS is less favorable in larger patients and for the deeper parts of the kidney due to sound beam attenuation and should thereby be used in addition to Dopplerbased ultrasound techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have been published in adult patients with carotid artery stenosis or ovarian torsion, and regarding the evaluation of vascularization in transplanted livers and kidneys [13][14][15][16]. Pediatric studies using BFS were reported for fetal congenital cardiopathies, femoral artery stenosis before catheterization in infants and anatomy of basal cerebral arteries in newborns [17][18][19]. The aim of this study was to compare BFS with CDS for the assessment of kidney transplant vascularization in children.…”
Section: Introductionmentioning
confidence: 99%
“…This can especially be useful for critical ill patients and young children requiring minimal handling. Examples of clinical routines with incorporation of US volumes are volumetric neonatal brain evaluation, neonatal basal artery evaluation, femoral artery evaluation in infants, growth plate assessment in adolescence, as well as general abdominal US in adults [ 20 , 21 , 22 , 26 , 27 , 28 ]. For these diagnostic protocols, technical settings including probe orientation, starting and ending position in case of free-hand translational probe movement, as well as rules for later offline read-out have been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of digital storage of exemplary single images, the recording of standardized US volumes containing continuous, thin through-plane slices in different techniques can be performed [ 19 ]. Volume US documentation facilitates offline reading as well as image interpretation in situations with complex vascular anatomy but, to the best of our knowledge, has not yet been systematically evaluated in LT monitoring [ 14 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…B-Flow imaging has been used previously to show better visualization of the femoral arteries in infants before catheter angiography. 19 Groth et al 20 also showed that B-Flow imaging was equal or better at vessel delineation compared to standard Doppler imaging methods to evaluate the basal cerebral arteries. Other studies have shown capability of B-Flow to visualize intravascular flow in various arteries.…”
Section: Discussionmentioning
confidence: 99%